2016
DOI: 10.3390/molecules21101414
|View full text |Cite
|
Sign up to set email alerts
|

Laurus nobilis, Zingiber officinale and Anethum graveolens Essential Oils: Composition, Antioxidant and Antibacterial Activities against Bacteria Isolated from Fish and Shellfish

Abstract: Several bacterial strains were isolated from wild and reared fish and shellfish. The identification of these strains showed the dominance of the Aeromonas hydrophila species in all seafood samples, followed by Staphylococcus spp., Vibrio alginolyticus, Enterobacter cloacae, Klebsiella ornithinolytica, Klebsiella oxytoca and Serratia odorifera. The isolates were studied for their ability to produce exoenzymes and biofilms. The chemical composition of the essential oils from Laurus nobilis leaves, Zingiber offic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 66 publications
3
34
4
Order By: Relevance
“…In our sample, the amount of sabinene was 12.2%, higher than in the essential oils analyzed by Derwich and coworkers [5], Snuossi and co-workers [11], and Yalcin [12] who found percentages of sabinene of 6.13, 3.5, and 6.13%, respectively. Linalool was found in concentrations comparable to previous studies [10,13] but in essential oil analyzed by Derwick and coworkers [5] linalool was not found.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…In our sample, the amount of sabinene was 12.2%, higher than in the essential oils analyzed by Derwich and coworkers [5], Snuossi and co-workers [11], and Yalcin [12] who found percentages of sabinene of 6.13, 3.5, and 6.13%, respectively. Linalool was found in concentrations comparable to previous studies [10,13] but in essential oil analyzed by Derwick and coworkers [5] linalool was not found.…”
Section: Discussioncontrasting
confidence: 74%
“…The comparison with most recent literature concerning the chemical composition of the essential oil of L. nobilis from other Mediterranean areas, showed substantial differences: 1,8-cineole percentage found (31.9%) is lower than the values recorded in other studies: Turkey 44.97% [10], Tunisia 56.0% [11], Cyprus 58.59% [12], Morocco 52.43% [5], but similar to Algerian essential oil (34.62%) [13]. In our sample, the amount of sabinene was 12.2%, higher than in the essential oils analyzed by Derwich and coworkers [5], Snuossi and co-workers [11], and Yalcin [12] who found percentages of sabinene of 6.13, 3.5, and 6.13%, respectively.…”
Section: Discussionmentioning
confidence: 66%
“…This finding was in accordance with those of Vazirian et al, 37 which proved that the main compound of the cinnamon essential oil is (E)-cinnamaldehyde (Table 2). Two compounds were wileyonlinelibrary.com/jsfa Snoussi et al 38 Radaelli et al 39 Vazirian et al 37 Snoussi et al 40 Snoussi et al 40 Valero et al 41 Giarratana et al, 33 identified in the cardamom-flavored olive oil: 1,8-cineole (57.1%) and -terpinyl acetate (20.6%), with similar percentages to those reported in cardamom essential oil by Snoussi et al 38 ( Table 2). In the rosemary-flavored olive oil, the major compounds were 1,8-cineole (60.8%), -pinene (9.1%), camphor (7.9%), and camphene (6.8%).…”
Section: Volatile Fraction Compositions Of Spiced Oilssupporting
confidence: 57%
“…Finally, 1,8‐cineole (66.0%), linalool (9.7%), β ‐pinene (9.7%), and α ‐pinene (6.9%) were the major compounds of the volatile fraction of olive oil flavored with laurel. As described in Snoussi et al, 1,8‐cineole is the main compound in laurel essential oil analysis (Table ), which is characterized by antibacterial activity …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation